SELF- PORTRAITS REGARDED AS THE VERY MANIFESTATION OF PSYCHOLOGICAL EVALUATION - Sah Jagati, Srishti; Shukla, Annpurna (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The artists who are both consciously and unconsciously involved embody their very own existence with impressions from their internal life. Out of many theories psychoanalysis can be used subjectively, for the existence of an individual in the process of becoming ‘I’. This theory of unconscious could be very personal. Using the impressions from the very theories of Freud is what I would like to write about in this research paper. His theory about psychoanalysis very particularly to study oneself or someone else would be like to ask for: What to see? What to Hear or Speak about? Express or repress? Depending upon a close observation alongside awareness on the life of many artists. Which has revealed from the past as they have been instinctive believers, of some other world. Making an apt sense of this is how any repressed emotions arises when explored to a deeper level of unconscious. As ‘I’ becomes the foundation to the core body the mind actively takes the possession to take actions for that very individual with holding a command on the body. The very idea of the Identity of the artist as an individual is related deeply to what the artist’s trying to express himself/ herself as one individual. And painting is the freedom of a platform using medium to paint without any restrictions. This paper tends to study the very idea of psychological journey of the artist. With the self-portraits inducing the very Identity of the artist through a critical evaluation on the artist.